En jämförelse mellan linjära och traditionella bedömningssystem hos hästar - Hedlund, Susanna (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
In Sweden the breeding organization for the Swedish Warmblood horse uses a traditional scoring system when evaluating horses. The horse is scored subjectively in relation to how good each trait is in relation to the breeding objective. Other countries, for example the Netherlands, instead use a linear scoring system. The linear scoring system evaluates the horse on a scale between two, for the breed, biological extremes which makes the evaluation more objective since the judges personal values does not influence as much. The breeding organization for the Swedish Warmblood is today planning a change towards a linear scoring system. The aim of this study was to look at the advantages and disadvantages of using a linear scoring system compared to using a traditional scoring system. The advantages of using a linear scoring system are that the evaluation becomes more objective and the horse is described on many detailed traits. This helps, for example, the owner of a mare to see the strengths and weaknesses of the mare, which can help when choosing the right stallion to compensate for those weaknesses. To make the system as objective as possible it is important to have judges who are well trained, judge similarly and that the horse is shown in a correct way. It is still an assessment done on where to place the horse on the scale, which makes even the linear scoring not totally objective.